Analysis of Motor Ability on The Ability To Kick The Ball In Football Games - Hasyim Hasyim; M. Imran Hasanuddin; M. Irfan Hasanuddin (JUARA : Jurnal Olahraga, 2023)
This study aims: 1) To find out how the motor skills of Syekh Yusuf's football school (SSB) students in Gowa Regency. 2) To find out how the ability to kick a football school student (SSB) Syekh Yusuf, Gowa Regency. 3) To find out the relationship between motor skills and the ability to kick a ball, SSB Syekh Yusuf students, Gowa Regency. The method used in this research is descriptive method with a quantitative approach to the type of correlational research. The population in this study were all students of SSB Syekh Yusuf, Gowa Regency. The sampling technique used simple random sampling consisting of 27 people. The results of this study: 1) The motor skills of Syekh Yusuf Gowa Regency Football School Students (SSB) tend to be in the very good category. 2) The ability to kick the ball in Syekh Yusuf's Football School Students (SSB) in Gowa Regency tends to be in the good category. 3) Motoric ability has a significant correlation with the ability to kick a ball in Syekh Yusuf's Football School Students (SSB), Gowa Regency, amounting to 20.2% with an R value of 0.449 and an Fcount of 6.311.